(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2025)
Photojournalist Sebastião Salgado (1944–2025) was renowned for his black-and-white series dedicated to labor (he became famous for his essay on the mines of Sierra Pelada, in Pará, Brazil), famine in Ethiopia, genocide in Rwanda, and other realities about the living conditions of the most vulnerable people in the many poor countries where he developed his vast photographic work. His photographs, charged with a mixture of emotion, beauty, and sadness, are published in books such as Other Americas (Contrejour and ELR, 1986), Workers (Phaidon, 1993), and in his projects Exodus (2005) and Genesis (2013), the latter dedicated to environmental protection. Translated with DeepL.com (free version)